Kabuki syndrome: clinical and molecular characteristics - Chong-Kun Cheon; Jung Min Ko (Korean Pediatric Society, 2015)
Kabuki syndrome (KS) is a rare syndrome characterized by multiple congenital anomalies and mental retardation. Other characteristics include a peculiar facial gestalt, short stature, skeletal and visceral abnormalities, cardiac anomalies, and immunological defects. Whole exome sequencing has uncovered the genetic basis of KS. Prior to 2013, there was no molecular genetic information about KS in Korean patients. More recently, direct Sanger sequencing and exome sequencing revealed KMT2D variants in 11 Korean patients and a KDM6A variant in one Korean patient. The high detection rate of KMT2D and KDM6A mutations (92.3%) is expected owing to the strict criteria used to establish a clinical diagnosis. Increased awareness and understanding of KS among clinicians is important for diagnosis and management of KS and for primary care of KS patients. Because mutation detection rates rely on the accuracy of the clinical diagnosis and the inclusion or exclusion of atypical cases, recognition of KS will facilitate the identification of novel mutations. A brief review of KS is provided, highlighting the clinical and genetic characteristics of patients with KS.